A Bioinspired Medical Adhesive Derived from Skin Secretion of Andrias davidianus for Wound Healing. (27th May 2019) - Deng, Jun; Tang, Yingying; Zhang, Qing; Wang, Chao; Liao, Min; Ji, Ping; Song, Jinlin; Luo, Gaoxing; Chen, Luo; Ran, Xiaohong; Wei, Ziming; Zheng, Liwen; et al.
Abstract: Existing surgical tissue adhesives on the market cannot meet the desired demand for clinical operations due to their limited adhesivity or undesired cytotoxicity. A new bioadhesive is derived from the skin secretion of Andrias davidianus (SSAD). This bioinspired SSAD has significantly stronger tissue adhesion than the fibrin glue and improved elasticity and biocompatibility when compared to the cyanoacrylate glue both ex vivo and in vivo. Additionally, the SSAD‐based adhesive decreases skin wound healing time and promotes wound regeneration and angiogenesis. The SSAD‐based adhesive is completely degradable, strongly adhesive, and easily produced from a renewable source. Based on these favorable properties, the SSAD‐based bioadhesive demonstrates potential as a surgical bioadhesive for a broad range of medical applications. Abstract : A new bioadhesive is derived from the skin secretion of the Chinese giant salamander . This bioinspired adhesive is completely degradable, strongly adhesive, and easily produced from a renewable source. Additionally, it is found to decrease skin wound healing time and promote wound regeneration and angiogenesis.